Biodiversitas Tumbuhan Herba Berdasarkan Variasi Ketinggian - Lailatul Hasanah Nasution; Melfa Aisyah Hutasuhut; Zahratul Idami (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the types, diversity, and distribution patterns of herbaceous plants based on variations in height. The method used is the survey method with the squared plot technique by purposive sampling at two heights of 1,009 masl and 1,144 masl with a plot size of 5 x 5 meters. The results showed that the herbaceous plants found at an altitude of 1,009 meters above sea level, namely 22 species with 14 families, the most species at an altitude of 1,009 meters above sea level were Impatiens sp., while the herbaceous plants found at an altitude of 1,144 meters above sea level, namely 15 species with 9 families, the most species at an altitude of 1,144 meters above sea level, namely Selaginella subalpine Aldrew. The diversity of herbaceous plants seen from the IVI value. The IVI value obtained at an altitude of 1,009 masl is found in Taenitis blechnoides Sw. of 36.268. At an altitude of 1,144 masl there is the highest IVI value, namely Selaginella subalpina Aldrew. of 48,400. The diversity index at an altitude of 1,009 masl was 2.313 while the diversity index at an altitude of 1,144 masl was 2,200. From the diversity index data for herbaceous plants, the diversity index was moderate. The distribution pattern of plants at an altitude of 1,009 masl is 2.66 and the pattern of distribution of herbaceous plants at an altitude of 1,114 masl is 2.89. The conclusion of the research is that the diversity of herbaceous plants in Batang Gadis Resort 6 National Park is classified as moderate, while the distribution of herbaceous plants found in Batang Gadis Resort 6 National Park is in groups. Keywords: Biodiversity, Herbs, Distribution Pattern, Altitude